O uso das histórias em quadrinhos da Monica’s gang como recurso para a produção de diálogos interculturais no ensino de inglês como LE - Rodrigues, F. R (2016)
This ethnographic case study aimed at identifying ways in which the comic books (CBs) of Monica’s Gang (Turma da Monica) in English triggered intercultural dialogues in English classes, and how the cultural meanings arising from the stories were interpreted by participants. Data were collected among five high school students in an extension course offered in the second half of 2014 at a school in the network of public schools in Goiânia, Goiás. Eight CB stories were read over the course of eleven classes. The data comprised audio recordings of the classes, a field diary recording the observations of the teacher-researcher, a survey completed during the fourth meeting, and interviews with the participants at the end of the course. This work is based mainly on theories of interculturalism in foreign language classrooms (Corbett, 2003; Kramsch, 1993, 2001, 2009), and on the dialogical perspective of Bakhtin (1981, 1992, 1997, 2010). The data revealed that the discussions triggered by the CBs led the participants to recognize other cultural contexts and to rethink their own culture(s), and also encouraged moments of reflection about cultural stereotypes and monolithic points of view. Moreover, analysis of the data revealed that the incompatibility of the micro-cultures of the participants’ learning and the teacher’s teaching had a significant influence on the findings. The present findings emphasize the necessity of teaching English with an intercultural discourse approach in mainstream English education, allowing opportunities for learners to position themselves in relation to different languages and cultures.